GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1437 species occurrences available in GBIF matching the query: TaxonKey: Chamaecrista serpens (L.) Greene. The dataset includes 1437 records from 94 constituent datasets: 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 3 records from HUEM - Herbário da Universidade Estadual de Maringá. 2 records from Phanerogamic Botanical Collections (S). 1 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 3 records from IAC - Herbário do Instituto Agronômico de Campinas. 22 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from SPSF - Herbário Dom Bento José Pickel. 8 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1 records from PRECIS. 3 records from UFP - Herbário UFP - Geraldo Mariz. 5 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from ICN - Herbário do Instituto de Ciências Naturais. 66 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 3 records from CESJ - Herbário Leopoldo Krieger. 31 records from MBM - Herbário do Museu Botânico Municipal. 10 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 26 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 4 records from Australia's Virtual Herbarium. 2 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 5 records from ALCB - Herbário Alexandre Leal Costa. 141 records from NMNH occurrence DwC-A. 2 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 3 records from ASE - Herbário da Universidade Federal de Sergipe. 9 records from UEC - Herbário da Universidade Estadual de Campinas. 5 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 15 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 1 records from Herbario del CIBNOR. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 126 records from Missouri Botanical Garden. 14 records from Natural History Museum (London) Collection Specimens. 4 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 2 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 7 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 1 records from Flora de las Barrancas del Cobre. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 2 records from Australian National Herbarium (CANB). 3 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 7 records from Arizona State University Vascular Plant Herbarium. 5 records from MEXU/Tipos de plantas vasculares. 2 records from United States National Plant Germplasm System Collection. 4 records from The System-wide Information Network for Genetic Resources (SINGER). 1 records from Herbarium de Geo. B. Hinton, México. 9 records from Harvard University Herbaria. 24 records from Herbario de la Universidad de Arizona, EUA. 8 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 90 records from Programa de repatriación de datos de ejemplares mexicanos. 18 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 34 records from Field Museum of Natural History (Botany) Seed Plant Collection. 84 records from UA Herbarium. 1 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Botany Division, Yale Peabody Museum. 2 records from HUTO - Herbário da Universidade de Tocantins. 1 records from Herbarium Senckenbergianum (FR). 2 records from MEXU/Flora de Oaxaca. 1 records from Herbier de la Guyane. 1 records from Herbario Amazónico Colombiano. 19 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 3 records from UPCB - Herbário do Departamento de Botânica. 1 records from HURB - Herbário do Recôncavo da Bahia. 1 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 7 records from TEPB - Herbário Graziela Barroso. 4 records from HTSA - Herbário do Trópico Semiárido. 14 records from HVASF - Herbário Vale do São Francisco. 1 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from HST - Herbário Sérgio Tavares. 61 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 9 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from Botany (UPS). 26 records from Instituto de Ciencias Naturales. 1 records from CNMT - Herbário Centro Norte Mato Grossense. 13 records from JPB - Herbário Lauro Pires Xavier. 6 records from EAC - Herbário Prisco Bezerra. 26 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 6 records from R - Herbário do Museu Nacional. 28 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 215 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from SLUI - Herbário Rosa Mochel. 12 records from UB - Herbário da Universidade de Brasília. 9 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 1 records from Instituto de ciencias naturales. 11 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 1 records from Vascular Plant Herbarium, Oslo (O). 20 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 2 records from EAN - Herbário Jaime Coelho de Moraes. 21 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 41 records from Geneva Herbarium – General Collection (G). 14 records from Instituto de Botánica Darwinion. 13 records from CAS Botany (BOT). 8 records from CPAP - Herbário CPAP. 2 records from MOSS - Herbário Dárdano de Andrade Lima. 1 records from HRCB - Herbário Rioclarense. 1 records from UESC - Herbário Universidade Estadual de Santa Cruz.
Keywords: GBIF; biodiversity; species occurrences